Software defined radios from smart(er) to cognitive - Pollin, Sofie (Signals and communication technology, 2011)
Mobile users need a variety of multimedia services, in very diverse geographical environments. The growing number of communication options within and across wireless standards is accommodating the growing volume and heterogeneity in wireless demands. On the other hand, advancement in radio technologies opening much more flexibility, a.o. through Software Defined Radios, opens up the possibility to realize mobile devices featuring multi-mode options at low cost and interesting form factors. It is crucial to manage the new degrees of freedom opened up in radios and standards in a smart way, such that the required service is offered at satisfactory quality, as efficiently as possible. Efficiency in energy consumption is paramount for battery powered mobile terminals, as well as in a broader, ecological context. Moreover, efficient usage of the spectrum is a growing prerequisite for wireless systems, and coexistence of different standards puts overall throughput at risk. The management of flexibility risks entails complexity which hampers the desired system agility. This book describes a systematic approach to master this challenge. Case studies show that this approach enables smart operation of radios realizing impressive efficiency gains, without hampering Quality-of-Service. Provides a concise overview of software defined radio technologies, opportunistic spectrum access and wireless standards; introduces opportunities and challenges related to the smart operation of radios in this context. Proposes a systematic approach to master the complexity of the desired agility. Demonstrates the application and benefits of this approach in recent systems, e.g. in WiFi context, and in the context of coexistence of different systems. Shows the need and potential in future scenarios, where cognitive radios will operate in an open spectrum environment.